Efeitos do tratamento de bezerras em aleitamento com somatotropina recombinante bovina sobre o eixo somatotrópico e parâmetros imunes - Anna Luiza Belli de Souza Alves Costa (2017)
Weaning may be associated with negative energy balance and body weight loss when calves are still immunological incompetent, predisposing them to infectious diseases. The aim of the present experiment was to investigate the effects of treatment of pre-weaned dairy calves with recombinant bovine somatotropin (rbST) on the somatotropic axis, on selected immune parameters, and hematology of calves around weaning. Thirty-six Holstein female calves were randomly assigned to receive 1.5 to 1.8 mg of rbST (Posilac, Elanco Animal Health, Greenfield, IN) per Kg of body weight or to receive injections of saline (Saline Solution 0.9%, Valley Vet Supply, Marysville, KS), every 7 days, from 21 to 63 days of life. Calves were fed milk replacer ad libitum from birth to 38 d of age (d 0), when progressive weaning started, and calves were weaned at 49 d of age. Calves were weighed at birth and weekly from 21 to 63 d of age, when wither height was also measured. Calves were vaccinated with 0.5 mg of ovalbumin on study d -17 and 4. Blood samples were collected on d -17, -14, -10, 0, 11, 14, 18, and 25. Polymorphonuclear leukocytes were isolated and challenged ex vivo with E. coli to determine phagocytosis and oxidative burst capacity. Additionally, expression of CD62L and CD18 by granulocyte, lymphocyte, and monocyte CD14+ were determined. Blood samples were also used to determine hematological parameters and concentrations of growth hormone, insulin like growth factor-1, insulin, glucose, non-esterified fatty and beta-hydroxybutyrate, haptoglobin, and IgG anti-ovalbumin. Calves treated with rbST had greater concentrations of growth hormone and insulin-like growth factor 1 from d -14 to 25 than control calves, whereas insulin, non-esterified fatty and beta-hydroxybutyrate concentrations did not differ. On d 0, glucose concentration was greater for rbST treated calves. Treatment did not affect PMNL phagocytosis and oxidative burst, but intensity of expression of CD62L and CD18 by granulocytes tended to be increased by rbST treatment. Treatment did not affect the IgG anti-ovalbumin concentration. Haptoglobin concentration was reduced in rbST treated calves on d 14 and there was a tendency for hematocrit to be lower in rbST treated calves. Treatment did not affect body weight, wither height and average daily gain, despite the fact that rbST treated calves had lower daily milk replacer intake. The relatively minor improvements in immune responses resulting from rbST treatment of weaning calves may not be sufficient to reduce the incidence of infectious diseases